Microalgae in design: Sustainable superfood production at domestic environment - Mgr. art. Tibor Antony (Slovak University of Technology, Faculty of Architecture and Design, 2020)
Biotechnology using Microalgae offers a promising model for producing food for the society in a sustainable manner. The article describes design research seeking possible implementation strategies of using the microalgae Spirulina in the design of tangible objects, specifically in the local, domestic environment. Microalgae’s most relevant properties, multi-functionality and environmentally effective growth are the parameters that predefine their use in the design for sustainable development. In terms of method-ology, the research is based on experiments and interdisciplinary approach combining various disciplines for consequent application of the acquired knowledge in the area of designing a new kind of object culture. The outcome therefore resonates with key questions related to sustainable development—effective food production with low envi-ronmental impacts, and profitability. The main idea of the described design research is a creation of new physical objects: such as a combination of a synthetic, industrially manufactured protective case and the living microalgae contained inside. This one specifically concentrates on microalgae Spirulina that is considered a superfood thanks to its exceptional nutritional content. The research results materialized in a fully func-tional prototype of the final product—a Spirulina Lamp.